SISTEM ISPO UNTUK MENJAWAB TANTANGAN DALAM PEMBANGUNAN KELAPA SAWIT INDONESIA YANG BERKELANJUTAN - Fahamsyah, Ermanto; Pramudya, Eusebius Pantja (Masyarakat Indonesia, 2018)
The implementation of ISPO certification system which has been running since 2011 in addition to having experienced various achievements and developments also encountered various obstacles, problems, challenges and demands. The formulation of the problems analyzed and answered in this study are: what aspects should be formulated in order to strengthen ISPO system? To analyze and answer the problem formulation is used framework thinking about legal system theory or Legal System Theory developed by Lawrence M. Friedman. The research method used in this study is more focused on normative legal research. Based on the analysis, it can be concluded that the aspects that must be formulated in order to strengthen ISPO system include: First, related to the aspect of law substance, ISPO system arrangement must be increased from the level of Minister of Agriculture Regulation to the level of Presidential Regulation. Through this Presidential Regulation is expected to become a stronger legal umbrella in the implementation of ISPO system. Second, in relation to aspects of its legal apparatus, the institutional mechanisms of ISPO certification shall be enhanced and strengthened. Third, from the legal culture aspect, there must be a common understanding about the definition and concept of sustainability in the management and development of oil palm Indonesia.